Liver abscess caused by ingestion of fishbone: A case report - Li, Jiangfa (Medicine (Baltimore), 2019)
RATIONALE: The penetration of a foreign body through the stomach wall and causing liver abscess is rare. A case of liver abscess caused by secondary bacterial infection was reported in the current study. PATIENT CONCERNS: A 58-year-old male patient had a history of eating fish and presented with recurrent fever with chills. The patient had a previous fever for 9 days without any obvious inducement and the highest body temperature rose to 40.8°C, along with fear of cold and chills. Body temperature declined to normal value after 5 days of infusion treatment (drugs were unknown) in the local clinic. Two days afterward, his body temperature again rose to 40.3°C at its highest. DIAGNOSIS AND INTERVENTION: Abdominal computed tomography (CT) showed that there was a quasicircular low-density focus in the left hepatic lobe which was most likely a liver abscess. A dense strip was found in proximity to the left hepatic lobe, implying the retention of a catheter in the upper abdominal cavity or a foreign body. On conditions of related preoperative preparations and general anesthesia, the left hepatic lobe was resected with the laparoscope. During the operation, a fish bone was found in the liver. Postoperative symptomatic and supportive treatment was carried out without antibiotics for liver protection. OUTCOMES: The patient was cured through surgical treatment and found to be in a good condition. The patient was successfully discharged and recovered well in the follow-up visit 3 months after the operation. LESSONS: Liver abscess caused by fish spines is rare. The contrast-enhanced CT of the abdomen and the minimally invasive abdominal operation both played critical roles in the diagnosis and treatment of the case. The general population, who mistakenly eat fish bones, should seek medical treatment as soon as possible.